Implementation of the Naïve Bayes Method in a Web-Based Fish Species Classification System - Rizki Suwanda; Muhammad Fikry; Said Fadlan Anshari (LPPM Universitas Malikussaleh, 2024)
The current fish resources are abundant, and the discovery of new species has increased the variety of fish in the ocean. These fish are categorized into three groups: demersal, pelagic, and reef fish, each with unique characteristics of their respective groups. The manual classification process for large datasets requires a long time and involves complex procedures. With the advent of data and information technology, it is now possible to recognize and identify several fish species found in the ocean, which can be classified into the three groups. To simplify this classification process, a web-based system has been developed to classify fish into these groups. The data to be processed in this research will be classified using the Naive Bayes method to address this issue. This technique utilizes large datasets to extract information that was previously unknown or inaccessible, and it can provide accurate information for various purposes. The data for this study will be collected from various internet references and direct data obtained from fish landing sites (TPI) in Lhokseumawe and North Aceh. Additionally, a literature review method will be used to complement the data analysis process. The development of the web-based system will be implemented to facilitate the classification of fish species based on the existing data.